APPLICATION OF GEOGRAPHIC INFORMATION SYSTEM (GIS) AND ANALYTICAL HIERARCHY PROCESS (AHP) IN SUITABILITY MAPPING OF SOME SELECTED CEREAL CROPS IN NORTHEASTERN NIGERIA - A., EZRA; M. LAKUMNA, THABBAL; A. A, ZEMBA; MAYOMI, IKUSEMORAN (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY GOMBE, 2023)
This research applied Geographical Information System (GIS) and Analytical Hierarchy Process (AHP) in delineation of places that are suitable for cultivation of some selected cereal crops. Climate (mean annual rainfall and temperature), soil texture, soil pH, slope and land use/ land cover maps were the criteria used in this study. In an attempt to produce the map of the selected criteria as layers for the suitability mapping, each selected criterion was analyzed and produced separately and were overlaid using Arc GIS 10.2. AHP was used to generate the priority of the criteria for crop cultivation in the region. Result of the study revealed that the highly suitable zone for cultivation of rice covered 47,152.75km2 (16.83%) of the total land area while suitability area for the cultivation of maize covered an area of 41,410.58km2 which represent 14.78% of the total land area in the region. Suitability map for cultivation of Sorghum on the other hand covered a total land area of 107,891.25 km2 (38.52%). In regards to this, it was concluded that over 70% of the region are highly suitable and suitable for cultivation of Rice, Maize and Sorghums. In addition, it was concluded that cultivation of sorghum is preferable in the region following the fact that it has the highest land area that is highly suitable for it cultivation compared to maize and sorghums. In the same vein, cultivation of rice, maize and sorghum is recommended in zones that are highly suitable in the region. It was also concluded that, analytical hierarchy process (AHP) has been tested to be a vital tool for suitability assessment and decision making in agricultural planning especially regarding the integration of different environmental factors for efficient crop production. Finally, application of GIS and AHP provide better information and guide decision makers on identifying suitable area for cultivation of different types of crops. As such, integration of the tools is recommended in related aggro-climatic.